Flexibilização e personalização de unidades habitacionais: Estudo de caso em Porto Alegre, RS - Fernandes, Rosana Da Silva (Universidade do Vale do Rio dos Sinos, 2012)
The construction sector has sought to suit the requirements of the real estate market to meet a new consumer profile, with new lifestyles, individualized work schemes and greater level of requirement. Ventures have been reconfigured and have come to consider issues such with more emphasis on user satisfaction and quality of building. Some of the options adopted by companies are the flexibility of design (different options of plants) and the possibility of customization of the units (modifications of plant layouts, finishing materials and installations). However, with the participation of users in the project settings, the quantity of interveners in the process and information exchange increased, causing failures in communication and feedback of design. This is one of the causes of rework and losses in the execution of the work, causing delays in the schedule of work and raising production costs. This study aims to investigate the processes of flexibility and customization of housing units in residential buildings vertical middle class sold in Porto Alegre, RS. The research was developed through a cases study with interviews and monitoring of works in four construction companies in Porto Alegre. In addition, a survey was conducted in the advertising sales of ventures to identify the level of flexibility and customization offered in real estate of the Metropolitan Region of Porto Alegre. From the analysis of this information have been proposed guidelines to improve the management of projects with possible modifications, such as mobile devices with wireless Internet, extranets design and BIM softwares, aiming at the efficiency of communication between interveners and reducing rework.
Keywords: Projeto; Gestão da informação; Flexibilidade; Personalização; Project; Managing information; Flexibility; Customization; BIM (Building Information Modeling); ACCNPQ::Engenharias::Engenharia Civil